Kepemimpinan Partisipatif Kepala Sekolah Penggerak pada Sekolah Menengah Atas (SMA) Negeri Kota Lubuklinggau - Rudi Erwandi; Marianita Marianita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to determine the participative leadership of driving school principals at State Senior High Schools (SMA) in Lubuklinggau City. This research uses a qualitative approach with phenomenological methods. The research subjects consisted of the Principal, Teacher Council, School Staff. Data collection techniques include observation, interviews, and documentation. The results of the research, the participatory leadership of the school principal driving Lubuklinggau City State High School (SMA) is as follows: able to create a good work climate, build two-way communication, verbal and non-verbal, provide motivation, and be able to collaborate with subordinates and make the right decisions. In conclusion, the school principal can build two-way verbal and non-verbal communication and can provide motivation, thereby creating a conducive work climate; with a conducive work climate, there will be good cooperation between the principal, teachers, and school staff. Keywords: Driving School, Participative Leadership